2014
DOI: 10.1037/prj0000015
|View full text |Cite
|
Sign up to set email alerts
|

Mediation analysis of critical time intervention for persons living with serious mental illnesses: Assessing the role of family relations in reducing psychiatric rehospitalization.

Abstract: Objective Critical Time Intervention (CTI) is a time-limited care coordination intervention designed to reduce homelessness and other adverse outcomes for persons living with serious mental illness during the transition period between institutions and community living. This study assesses whether CTI improves the quality of family relationships between family members and individuals living with serious mental illness, and examines whether changes in quality of family relationship mediated the association betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 40 publications
1
20
0
2
Order By: Relevance
“…Much of the literature in our recent systematic review (8) problematized readmission, post-discharge suicide, medication management, and symptom management associated with discharge from acute mental health services (8,17,31). Yet we found that staff considered fear, blame, and clarity about each group's expectations to be root-problems from an interagency perspective.…”
Section: Discussionmentioning
confidence: 99%
“…Much of the literature in our recent systematic review (8) problematized readmission, post-discharge suicide, medication management, and symptom management associated with discharge from acute mental health services (8,17,31). Yet we found that staff considered fear, blame, and clarity about each group's expectations to be root-problems from an interagency perspective.…”
Section: Discussionmentioning
confidence: 99%
“…We examined baseline demographic and social factors for potential associations with psychiatric rehospitalization: increased age, male gender, marital status (not living with spouse/long-term romantic partner), availability of family support (whether family was not actively available to help with care for patient either in-person or by telephone) and 'supervised living' (living in a supervised residence, nursing home or group home versus living independently) (Mercer et al, 1999;Durbin et al, 2007;Priebe et al, 2009;Lin et al, 2010a;Lin et al, 2010b;Schmutte et al, 2010;Sanchez et al, 2013;Jaramillo-Gonzalez et al, 2014;Tomita et al, 2014). We also investigated psychiatric variables, including history of psychiatric hospitalizations prior to index (baseline) psychiatric admission, non-adherence to medication, alcohol abuse, other substance abuse (recreational drugs or opioids), psychiatric diagnosis (bipolar disorder, psychotic disorder, depression), length of index admission, use of ECT during index admission, having a higher number of comorbid medical illnesses and cognitive dysfunction (documented mild cognitive impairment or dementia) (Ayuso-Gutierrez and del Rio Vega, 1997; Heeren et al, 2002;Kolbasovsky et al, 2007;Prince et al, 2008;Yussuf et al, 2008;Lin et al, 2010b;Lin et al, 2010a;Nordenskjold et al, 2011;Hendrie et al, 2013;Sanchez et al, 2013;Forcada et al, 2014).…”
Section: Potential Predictors Of Psychiatric Re-hospitalizationmentioning
confidence: 99%
“…In non‐geriatric samples, a number of predictors for psychiatric re‐hospitalization have been consistently found: male gender, poor treatment adherence, longer length of stay, multiple previous admissions and the diagnosis of a mood or primary psychotic disorder (Ayuso‐Gutierrez and del Rio Vega, ; Kolbasovsky et al, ; Yussuf et al, ; Lin et al, ; Lin et al, ). Other factors have also been identified in young adult samples: living in a supervised setting, poor family relationships, unemployment, poor psychosocial support, substance use and electroconvulsive therapy (ECT) (Priebe et al, ; Schmutte et al, ; Nordenskjold et al, ; Sanchez et al, ; Tomita et al, ). Frequent psychiatric hospitalization is costly for the healthcare system and can significantly impact patients' quality of life (Bartels and Pratt, ; Stensland et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Durch CTI ließ sich auch das Risiko stationärer Wiederaufnahmen deutlich senken [39], und gleichzeitig der wahrgenommene Zugang zu Behandlern und Versorgungsleistern verbessern [59]. Positiv moderierend wirkte sich dabei eine größere Kontaktdichte zu Familienangehörigen und eine daraus resultierende größere Zufriedenheit im Bereich familiärer Beziehungen aus [60]. Eine vergleichbare Intervention in New York City führte ebenfalls zu einer deutlichen Reduktion wohnungsloser Nächte gegenüber herkömmlicher Versorgung.…”
Section: Kurzzeitinterventionenunclassified